Landslide response to the 27 October 2012 earthquake (MW 7.8), southern Haida Gwaii, British Columbia, Canada - Sophia Barth; Marten Geertsema; Alexandre R. Bevington; Alison L. Bird; John J. Clague; Tom Millard; Peter T. Bobrowsky; Andreas Hasler; Hongjiang Liu (Landslides, 2020)
In this paper, we examine the influence of the 27 October 2012, M w 7.8 earthquake on landslide occurrence in the southern half of Haida Gwaii (formerly Queen Charlotte Islands), British Columbia, Canada. Our 1350 km 2 study area is undisturbed, primarily forested terrain that has not experienced road building or timber harvesting. Our inventory of landslide polygons is based on optical airborne and spaceborne images acquired between 2007 and 2018, from which we extracted and mapped 446 individual landslides (an average of 33 landslides per 100 km 2 ). The landslide rate in years without major earthquakes averages 19.4 per year, or 1.4/100 km 2 /year, and the annual average area covered by non-seismically triggered landslides is 35 ha/year. The number of landslides identified in imagery closely following the 2012 earthquake, and probably triggered by it, is 244 or an average of about 18 landslides per 100 km 2 . These landslides cover a total area of 461 ha. In the following years—2013–2016 and 2016–2018—the number of landslides fell, respectively, to 26 and 13.5 landslides per year. In non-earthquake years, most landslides happen on south-facing slopes, facing the prevailing winds. In contrast, during or immediately after the earthquake, up to 32% of the landslides occurred on north and northwest-facing slopes. Although we could not find imagery from the day after the earthquake, overview reconnaissance flights 10 and 16 days later showed that most of the landslides were recent, suggesting they were co-seismic.